2022
DOI: 10.3390/ijms231911284
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Exosomes in Chronic Rhinosinusitis: A Systematic Review

Abstract: The pathophysiology of chronic rhinosinusitis (CRS) is multifactorial and not entirely clear. The objective of the review was to examine the current state of knowledge concerning the role of exosomes in CRS. For this systematic review, we searched PubMed/MEDLINE, Scopus, CENTRAL, and Web of Science databases for studies published until 7 August 2022. Only original research articles describing studies published in English were included. Reviews, book chapters, case studies, conference papers, and opinions were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 144 publications
0
4
0
Order By: Relevance
“…In recent years, knowledge of the role of EVs in many inflammatory diseases and cancers has grown rapidly [ 117 , 118 ]. EVs isolated from the plasma of HNSCC patients provide information on tumour status, genetic complexity and immune dysfunction [ 119 ], but also on the molecular mechanisms involved in cancer metastasis and resistance to therapy [ 120 , 121 , 122 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, knowledge of the role of EVs in many inflammatory diseases and cancers has grown rapidly [ 117 , 118 ]. EVs isolated from the plasma of HNSCC patients provide information on tumour status, genetic complexity and immune dysfunction [ 119 ], but also on the molecular mechanisms involved in cancer metastasis and resistance to therapy [ 120 , 121 , 122 ].…”
Section: Discussionmentioning
confidence: 99%
“…As epigenetic changes are tissue- or cell-specific, NP tissue, HNEpC of the inferior turbinate or unciform process mucosa, and extracellular vesicles from nasal lavage fluid have been adopted in recent studies ( Steelant et al, 2019 ; Shin et al, 2020 ; Cha et al, 2021 ; Park et al, 2022 ). Systematic review has also shown growing evidence of the role of exosome miRNAs in the development of CRS ( Dzaman and Czerwaty, 2022 ). Epigenetic modifications happen in a wide spectrum of organs and diseases, so the sensitivity and specificity of epigenetic biomarkers obtained by traditional high-throughput techniques are low.…”
Section: Concluding Remarks and Suggestions For Future Workmentioning
confidence: 99%
“…The traditional extraction methods for exosomes are mainly as follows: ultracentrifugation, ultrafiltration centrifugation, chromatography, precipitation, immunoaffinity chromatography, and immunomagnetic beads. The advantages of ultracentrifugation are low cost-effectiveness, no risk of contamination, and the ability to extract larger amounts of exosomes [ 46 ]. But this method consumes time due to continuous centrifugation [ 47 ].…”
Section: Optimization Strategy Of Exosomes In Clinical Application An...mentioning
confidence: 99%